Comparative Analysis of Unemployment Dynamics in Developed EU Countries and Developing African Countries - Chola, Kosam Chishimba; Formánek, Tomáš; Lacko, Jindřich; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The paper presents a comparative analysis of unemployment dynamics in the African Union (AU) and European Union (EU) regions, focusing on key macroeconomic and demographic factors such as Gross Domestic Product (GDP) growth, youth unemployment, and labour market participation. Using panel data models (Fixed Effects, Random Effects and Generalised Method of Moments), the study finds that while GDP growth significantly reduces unemployment in both regions, the impact is stronger in the EU. Youth unemployment is a major driver of overall unemployment in both regions, but in Africa, high tertiary education enrolment is surprisingly associated with higher unemployment due to a mismatch between skills and job market demands. In addition to these key findings, the analysis highlights the role of wealth utilisation which measures how effectively natural resources are converted into economic output to lower unemployment in Africa, suggesting that efficient resource management can drive job creation. The study also reveals that unemployment in the EU is persistent, with past levels strongly influencing current rates, underscoring the importance of sustained, long-term policy measures. Moreover, trade openness in Africa appears to increase unemployment, likely due to short-term disruptions in local labour markets, while immigration in the EU contributes to unemployment, pointing to challenges in integrating immigrant workers. Policy recommendations include targeted youth employment initiatives and educational reforms in AU countries, and flexible labour market policies and technological adaptation strategies in the EU.
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses